Information exposure relating with reading behavior on packaged food product among college students in Fikes Uhamka - Aisya Desy Novitamanda; Nanang Prayitno; Izna Nurdianty (ARGIPA (Arsip Gizi dan Pangan), 2020)
In this era, food products had a high interest in the community because it is easy to consume but not followed by behavior to read the food label. The objective of this study was to analyze the relationship between food label knowledge and information exposure with food label reading behavior on college students in FIKES UHAMKA. This study was quantitative research with a cross-sectional design. This study conducted in July–August 2019 with 239 subjects. Data analyzed used Chi-Square statistical test. The result showed 52,7% of subjects always reading food labels. Food label knowledge did not have a relationship with food label reading behavior. Information exposure variable has a relationship with food label reading behavior.